8 - Review: Define and Rule: Native as Political Identity - Lwazi Siyabonga Lushaba, (African Sociological Review, 2014)
Define and Rule: Native as Political Identity, by Mahmood Mamdani. USA: Harvard University Press, 2012. ISBN No: 978 0 674 05052 5 – Hardcover, pp. 154.